1986
DOI: 10.1523/jneurosci.06-06-01814.1986
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of directional specificity in the regeneration of lamprey spinal axons

Abstract: The projection patterns of regenerating spinal axons in the larval sea lamprey (Petromyzon marinus) were determined by intracellular injection of HRP. Four hundred and eighty-six of 562 stained axons and axon-like neurites (87%) arising from Muller and Mauthner axons, giant interneurons, and dorsal cells terminated in an orientation similar to that of their counterpart control cells. Therefore, lamprey spinal axons regenerate selectively along their normal projection paths. During the first 4 weeks of recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 23 publications
(29 reference statements)
6
30
1
Order By: Relevance
“…Animals in which hemisection was judged to be incomplete or to extend far beyond the midline at the time of surgery were discarded, but slight overhemisection was accepted and even presumed. To block regeneration of transected reticulospinal axons, 5 mm of spinal cord caudal to the transection was excised, leaving a large gap through which transected axons were incapable of regenerating (Mackler et al, 1986). Successful regeneration of reticulospinal axons requires the presence of glial elements in the lesion site (Lurie and Selzer, 1991b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals in which hemisection was judged to be incomplete or to extend far beyond the midline at the time of surgery were discarded, but slight overhemisection was accepted and even presumed. To block regeneration of transected reticulospinal axons, 5 mm of spinal cord caudal to the transection was excised, leaving a large gap through which transected axons were incapable of regenerating (Mackler et al, 1986). Successful regeneration of reticulospinal axons requires the presence of glial elements in the lesion site (Lurie and Selzer, 1991b).…”
Section: Methodsmentioning
confidence: 99%
“…Reticulospinal axons of larval and adult lampreys regenerate selectively in their correct directions across complete transections of the spinal cord Mackler et al, 1986;Lurie and Selzer, 1991a). By 10 weeks after spinal transection, larval lampreys recover behavioral functions (Rovainen, 1976;Selzer, 1978) that are mediated by the formation of synapses with appropriate neurons distal to the site of injury (Mackler and Selzer, 1987).…”
Section: Heterogeneity Of Cns Axon Regenerationmentioning
confidence: 99%
“…Micro-electrodes filled with 4-8 % (w/v) horseradish peroxidase (HRP; Yin & Selzer, 1983) (Yin, Mackler & Selzer, 1984;Mackler et al 1986). The experimental design is illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…were selected. Previous experiments have shown that lamprey spinal axons regenerate preferentially in their normal rostral-caudal direction and on the correct side of the spinal cord Mackler et al 1986). The dendritic trees of g.i.s span the entire width of the spinal cord.…”
Section: Selectivity Of Synapse Formation By Regenerating Lamprey Axonsmentioning
confidence: 99%
See 1 more Smart Citation